Brick wall construction of single storey house / Muhammad Raif Danish Md. Robyzaquri - Md. Robyzaquri, Muhammad Raif Danish (Universiti Teknologi MARA, Perak, 2022)
A wall is a structural feature that divides or encloses a space and, in building construction, forms the room or building's perimeter. Traditional masonry construction required exterior walls to support the weight of floors and roofs, but modern steel and reinforced concrete frames, as well as heavy timber and other skeletal structures, only require exterior walls for shelter and sometimes do away with them entirely on the ground floor to allow easier access. This report will discuss about wall construction. This report was conducted for The Construction of Single Storey House at Kampung Kadok Dalam 16450 Ketereh Kelantan. The objective of this report is to analyze the construction of wall and the way how it carried out. It will focus on the whole process of wall construction. It also investigate the equipment and machinery in the methods of wall construction and to determine duration that have been used for the construction. This report will also look to at the problem and the solution in wall construction that would fulfill the criteria of wall.